Synchronization Interfaces for Improving Moodle Utilization - Linawati Linawati; Gede Sukadarmika; GM Arya Sasmita (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2012)
Many universities have applied e-learning on more than one LMS (learning management system) platforms such as Wordpress and Moodle. In addition, difficulties implementations in developing countries have occurred. Those are mainly caused by limitations and expensive of internet infrastructure. Therefore to increase Moodle application as an e-learning system, the paper proposed two synchronization interfaces. The first interface is for Moodle and Wordpress. This assists teachers to migrate their learning material in their blog in Wordpress into Moodle. Second interface is for Moodle portable performing offline LMS and Moodle performing online LMS. Moodle portable was installed in teachers and students notebooks. Moodle itself was installed and run in e-learning server. The aim is to improve Moodle utilization in the class. The results showed satisfied outcomes. Students and teachers could employ the interfaces easily and secure as they have to login using student/teacher ID, course ID, username and password.